2007
DOI: 10.1152/ajpgi.00356.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of myosin regulatory light chain and Rac1 in the migration of polyamine-depleted intestinal epithelial cells

Abstract: We have previously shown that polyamine depletion decreased migration, Rac activation, and protein serine threonine phosphatase 2A activity. We have also shown that polyamine depletion increased cortical F-actin and decreased lamellipodia and stress fibers. In this study, we used staurosporine (STS), a potent, cell-permeable, and broad-spectrum serine/ threonine kinase inhibitor, and studied migration. STS concentrations above 100 nM induced apoptosis. However, in polyamine-depleted cells, a lower concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Orange ovals, SC nuclei; blue circles, axons; red lines, inhibition; blue arrow, activation. describing the presence of its endogenous targets (myosin II and/ or MLC) in the nucleus of human and rodent cells (Li and Sarna, 2009;Ray et al, 2007). MLCK activity has been shown to be necessary for TNFa-dependent NFkB activation and amplification of pro-survival signals (Wadgaonkar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Orange ovals, SC nuclei; blue circles, axons; red lines, inhibition; blue arrow, activation. describing the presence of its endogenous targets (myosin II and/ or MLC) in the nucleus of human and rodent cells (Li and Sarna, 2009;Ray et al, 2007). MLCK activity has been shown to be necessary for TNFa-dependent NFkB activation and amplification of pro-survival signals (Wadgaonkar et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This assay was carried out as described previously. 35,36 Cells grown in control, DFMO, or DFMO plus putrescine containing media were serum starved for 24 h before the experiment. Six-well plates containing a confluent monolayer of cells were marked in the center (along the diameter) with a marker.…”
Section: Methodsmentioning
confidence: 99%
“…Rac1 activity was determined by pull down assay as described previously. 36,37 GST-PAK fusion protein bound with the glutathione agarose beads was mixed with cell lysate (200 µg). The binding was allowed to proceed for 1.5 h at 4°C, the beads were washed with lysis buffer and the amount of GTP-Rac1 bound was analyzed by SDS-PAGE and western blot using Rac1 specific antibody.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Our and other results (Even-Ram et al 2007;Vidali et al 2006) have identified Rac-1 activation as one of these signals. This notion is supported by reports that assaulting the organization of the actin cytoskeleton alters Rac-1 activation/expression (Di Ciano et al 2002;Katsumi et al 2002;Vitale and Carbajal 2004;Ray et al 2007;Sharma and Mayer 2008;Desai et al 2008;Baumer et al 2008).…”
Section: Myosin II Isoforms and Cell Shapementioning
confidence: 66%